Study of moral and prosocial norms in sport - Belov, M. S.; Kislyakov, P. A.; Silaeva, O. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the attitude of athletes to the adoption of prosocial and moral norms in sports in the conditions of competitive activity.